Utilizing a risk assessment and mitigation measure checklist to reduce the threat of coronavirus disease-2019 outbreak in social gatherings - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The impact of the Corona Virus Disease-2019 (COVID-19) pandemic extends beyond the health dimension alone and has also simultaneously affected the socioeconomic domains. It is noteworthy that in some of the nations, outbreaks of the disease have been linked with religious gatherings, which acts as a ground for rapid transmission of the disease, if appropriate prevention and control measures are not taken. Under ideal scenario, as long as the threat of the pandemic looms over the world, it is best to avoid any social or religious gatherings and encourage virtual meetings with the help of the religious leaders. However, if the gathering is a must and cannot be avoided, it should be planned after conducting the risk assessment and checking for mitigation measures. In conclusion, it is extremely important that a systematic approach of risk assessment and assessment of mitigation measures is done before any social gathering is planned, as there is a potential risk of onset of new chain of transmission of COVID-19 infection, which in turn can have serious after effects.